2017
DOI: 10.5433/1679-0359.2017v38n3p1361
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity effect of Auxemma oncocalyx fraction and its active principle oncocalyxone A on in vitro culture of caprine secondary follicles and in vitro oocyte maturation

Abstract: The extract of Auxemma oncocalyx (A. oncocalyx) and its main component, oncocalyxone A (onco A), possess anti-tumoral activity that may affect fertility. There is limited literature on the action of these substances regarding caprine folliculogenesis. In this study, we evaluated the effect of A. oncocaly and onco A on the in vitro culture of isolated secondary follicles (Experiment 1) and on the in vitro maturation (IVM) of oocytes from caprine antral follicles grown in vivo (Experiment 2). Isolated secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In this study, we observed a significant increase in mRNA levels for GDF9 , CCNB1 , PARN , cMOS , eIF4E , and H1FOO in oocytes derived from secondary follicles grown for 18 days. Several variables may affect the outcome of follicle culture in vitro (Mbemya et al, ), such as the culture base media composition (McNatty, Reader, Smith, Heath, & Juengel, ; Santos et al, ) and supplementation (Ferreira et al, ), the animal model (Magalhães et al, ), the culture system (Araújo, Gastal, Figueiredo, & Gastal, ), the follicular category (Magalhães‐Padilha et al, ), reactive oxygen species (ROS) production (Leiva‐Revilla et al, ), and activation or silencing of genes encoding antioxidant defense enzymes, growth and progression of meiosis (Dalton, Shertzer, & Puga, ). Therefore, an increase of the expression of these genes in oocytes may be a good indicator of the viability of in vitro culture secondary follicles, providing support to oocyte development.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed a significant increase in mRNA levels for GDF9 , CCNB1 , PARN , cMOS , eIF4E , and H1FOO in oocytes derived from secondary follicles grown for 18 days. Several variables may affect the outcome of follicle culture in vitro (Mbemya et al, ), such as the culture base media composition (McNatty, Reader, Smith, Heath, & Juengel, ; Santos et al, ) and supplementation (Ferreira et al, ), the animal model (Magalhães et al, ), the culture system (Araújo, Gastal, Figueiredo, & Gastal, ), the follicular category (Magalhães‐Padilha et al, ), reactive oxygen species (ROS) production (Leiva‐Revilla et al, ), and activation or silencing of genes encoding antioxidant defense enzymes, growth and progression of meiosis (Dalton, Shertzer, & Puga, ). Therefore, an increase of the expression of these genes in oocytes may be a good indicator of the viability of in vitro culture secondary follicles, providing support to oocyte development.…”
Section: Discussionmentioning
confidence: 99%
“…Several variables may affect the outcome of in vitro follicle culture such as the culture base media composition [9, 10] and supplementation [11]; the animal model [8]; culture system [1, 12]; follicular category [13, 14] and reactive oxygen species (ROS) production [15], leading to oxidative stress. Many authors have shown that an increase of glutathione peroxidase (GPx) can represent a cellular transcriptional response to ROS [16], such as an activation or silencing of genes encoding antioxidant defense enzymes, growth and progression of meiosis [17].…”
Section: Introductionmentioning
confidence: 99%